Successful pregnancy outcome in a patient of chronic myeloid leukemia on imatinib therapy - Singhal, Manisha; Meena, Khushbu; Bharadwaj, Neelam; Mundaliya, Renuka; Agarwal, Shruti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Pregnancy and cancer is a complex situation. The coincidence chronic myeloid leukemia (CML) and pregnancy is an uncommon event, in part because CML occurs mostly in older age group. The management of CML, during pregnancy is a difficult problem because of potential effects of therapy on the mother and foetus. Imatinib, a tyrosine kinase inhibitor induces dramatic hematologic and cytogenetic responses in CML, but it is not recommended for use in pregnancy or if the patient plans to conceive. In literature there are very few reports of successful outcome of pregnancy while on imatinib. In this report we describe a successful pregnancy and labor under treatment with imatinib in a known case of CML.